Safety of “Sachet Water” and Raw Milk - Ofori-Adjei, D. (Ghana Medical Journal, 2007)
In recent times non-biodegradeable materials, especially containers of commercially baged drinking water has been a source of environmental concern to public health institutions and metropolitan, municipal and district administrations. These containers are not properly disposed of after use and choke drains and fill refuse dumping sites. Apart from the environmental problems these containers are sources of stagnant water conducive to the breeding of mosquitoes. The regulatory environment in which manufacturers of sachet water operate has seen marked challenges and there is proliferation of manufacturers with little or no control of the industry.
Journal Article
Keywords: Sachet Water; Raw Milk; health institutions; metropolitan